History in Popular Magazines : Negotiating Masculinities, the Low of the Popular and the High of History - Axelsson, Bodil (My University, 2012)
This article explores how the low of the popular and the high of history intersect to negotiate masculinities in the nexus of politics and war in a Swedish history magazine. It investigates the content of the magazine’s form and argues that it produces a kaleidoscopic take on the past which begs the reader to go along with the ads to buy another book, travel to one more historical site, buy a DVD or go to the movies, to turn the page, or to buy another issue of the magazine. Two articles, biographical in their outset, provide the basis for an analysis on how masculinities are negotiated by displaying political and military leaders in contradictory ways and enabling multiple entrance points for the contemporary reader and spectator. Articles on great men produce cultural imaginaries of warlords and political leaders by drawing on layers of historically contingent ways for men to act in public and private spheres and connecting late modern visual celebrity culture to the cults of fame in earlier centuries.
Keywords: 306 Kultur und Institutionen; history magazines; popular culture; popular history; masculinities; cultural imaginaries; celebrity culture; the content of the form